2017
DOI: 10.1080/17429145.2017.1371798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bio fertilizer and nano Zn-Fe oxide on physiological traits, antioxidant enzymes activity and yield of wheat (Triticum aestivumL.) under salinity stress

Abstract: In order to evaluate the effects of nano Zn-Fe oxide and bio fertilizer on physiological traits, antioxidant activity and yield of wheat under salinity stress, a factorial experiment was conducted based on RCBD with three replications.Treatments were included salinity in three levels (no-salt, salinity 25 and 50 mM NaCl), four bio fertilizers levels (no bio fertilizer, seed inoculation by Azotobacter, Azosperilium, Pseudomonas) and nano oxide (without nano, application of nano Zn oxide, nano Fe oxide and nano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 57 publications
(58 reference statements)
6
50
0
Order By: Relevance
“…Consequently, it was found that using the combination of PGPR side-by-side with SA was efficient in mitigating water deficit conditions and improving the nutritional status of plants. The results of the present study are consistent with the results of [39], which showed that foliar spraying of salicylic acid has the capability to produce enzymatic and non-enzymatic metabolites to detoxify the detrimental impacts of reactive oxygen species, produce of antioxidant compounds, and seed inoculation by microbes that can fix the nitrogen in the soil under harsh conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, it was found that using the combination of PGPR side-by-side with SA was efficient in mitigating water deficit conditions and improving the nutritional status of plants. The results of the present study are consistent with the results of [39], which showed that foliar spraying of salicylic acid has the capability to produce enzymatic and non-enzymatic metabolites to detoxify the detrimental impacts of reactive oxygen species, produce of antioxidant compounds, and seed inoculation by microbes that can fix the nitrogen in the soil under harsh conditions.…”
Section: Discussionsupporting
confidence: 92%
“…[29] reported that under high salinity level (5.55 dS m −1 ), biofertilizer and 0.8 g l −1 nano-zinc oxide increased grain yield of Triticale (a hybrid of wheat and rye) by 39% compared with the control (without any additions). Application of nano-zinc at rates of 25 or 50 mg l −1 caused significant changes in fresh and dry weight as well as in relative water content of rice [30] in biomass production of sunflower [31], in grain yield of wheat under salinity stress [32] and in yield of maize under drought [33]. These enhancements in growth, yield and quality of different plant kinds with nano-fertilizer addition may be due to (1) increasing the nutrient use efficiency [34,35], (2) minimizing soil toxicity induced by overdosage of fertilizer addition [34], (3) improving levels of antioxidant enzyme activities, consequently protecting plants from damage caused by reactive oxygen species [30].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, antioxidative enzymes like APX and CAT are the most important components in the scavenging system of ROS [75]. Also, [32], reported that the activities of the antioxidative enzymes such as CAT and APX increased under salt stress in plants and a correlation of these enzyme levels and salt tolerance exist. It has been found that plants inoculated with bacterial strains showed high antioxidant enzymes activity which contributed to enhance plant protection against salt stress by eliminating hydrogen peroxide from salt-stressed roots [31].…”
Section: Discussionmentioning
confidence: 99%
“…Noorieh et al have reported that PGPR species like Azotobacter and Pseudomonas increased the growth and biomass of canola (Brassica napus L.) by regulating the oxidative stress enzymes and essential nutrient under salinity stress [31]. Babaei et al showed that application of biofertilizers (A. chrocoocum strain 5 (F2), Azosperilium lipoferum strain OF (F3) and Pseudomonas putida strain 186 (F4) and nano Zn-Fe oxide improved grain yield, chlorophyll content, antioxidant enzyme activity, proline and soluble sugars under different levels of salinity (no-salt, salinity 25 and 50 mM NaCl) conditions [32].…”
Section: Introductionmentioning
confidence: 99%